Über die vielfalt von Chrysolina purpurascens-formen in Slowenien (Coleoptera: Chrysomelidae) - Kippenberg, Horst (Acta entomologica slovenica (Ljubljana), 2005)
Chrysolina purpurascens shows various aedeagus types in Slovenia which coexist in some populations. The reason for that unusual diversity can be seen in the existence of sinks, so-called "dolines". Their special climatic situation possibly enabled relict populations to survive warm interglacial periods.
Keywords: Coleoptera; hrošči; morfologija; Slovenia; Slovenija